Measurement by Air Data System of Spatial Position and Direction of Aircraft - Karimli, T.I. (Herald of Azerbaijan Engineering Academy, 2022)
The article gives a review of air data system, the perspectives for expanding the improvement of its functional capability are determined. The conditions for increasing the technical capabilities of smart air signal systems, produced on the basis of advanced technology used on the 5th generation US military aircraft and civil aircraft, have been determined. The installation of additional air pressure receivers on smart air signal systems, along with the measured altitude and speed parameters, presents the possibilities and algorithms for measuring the angles of roll, pitch, yaw and lateral speed of aircraft, which are the necessary primary flight parameters.